Management of inferior vena cava injury in a non specialized tertiary hospital-a case report - Rahman, ASM Tanjilur; Rahman, ASM Zahidur; Shaha, Ratan Kumar; Biswas, Swapan Kumar; Biswas, Sushit Kumar; Sen, Sumon Kumar; Biswas, Gonopati; Rahman, Md Mahfuzur (Faridpur Medical College Journal, 2015)
Abdominal vascular injury are among the most challenging and lethal injuries in the traumatized patients. Inferior vena cava (IVC) is the most frequently injured vein during the blunt or penetrating trauma. Ligation of IVC, venorrhaphy, venoplasty, end to end anastomosis, endovascular stenting or graft interposition should be considered in selected cases. However most of the procedures require special setting and surgical team. Relatively simple procedure e.g. venorrhaphy produces narrowing of lumen in many cases. Ligation of IVC may result in thrombosis and embolism thus increases morbidity of patients. Here, in the present case the authors report a patient with IVC injury repaired by venoplasty (cavaplasty) with great saphenous vein patch in a non specialized tertiary hospital and it can be performed by a team led by general surgeon. Faridpur Med. Coll. J. 2014;9(1): 53-55